The genus Sigmatoneura Enderlein (Psocoptera: Psocidae), with two new species from China LUXI LIU, FASHENG LI & ZHIQI LIU - Liu, Luxi; Li, Fasheng; Liu, Zhiqi (Zootaxa, 2011)
The genus Sigmatoneura Enderlein is reviewed. Two new species, S. pinbiensis sp. nov. and S. aquilis sp. nov., are described from China. The distribution pattern of the 16 Chinese species is discussed briefly, with a distribution map. Identification keys for males and for females of Chinese species are provided.